LEVEL OF LEARNING DISCIPLINE OF CLASS XI HIGH SCHOOL STUDENTS - Firmansyah, Muhammad Iqbal; Suhendri, Suhendri; Dina, Farah (Jurusan Bimbingan dan Konseling, 2024)
The undisciplined behavior carried out by some students includes coming to school late, not going to school or skipping class, not doing school assignments. This study aims to understand the level of learning discipline of eleventh grade high school students. The research methodology applied is quantitative descriptive analysis. The research population was all eleventh grade high school students, the research sample was 186 students. Data analysis was carried out calculating the score of the learning discipline scale through filling out questionnaires that had been distributed to the research population. The results showed that 128 students (68.8%) were in the moderate category related to the level of learning discipline. Students need to be given an understanding of the awareness of the importance of studying hard. And it is necessary to arrange learning methods that are in accordance with the characteristics of students.